URGENSI PENGAJARAN ISLAM NUSANTARA PADA PROGRAM STUDI VOKASIONAL DI PERGURUAN TINGGI DALAM MENANGKAL RADIKALISME - Muhammad Asrori (Kuttab : Jurnal Ilmu Pendidikan Islam, 2017)
Islam Nusantara (Islam of the archipelago) is a new term having recently captivated especially Muslim scholars. Islam Nusantara is the discourse about Islam as a religion having an encounter with tradition in the archipelago. Such encounter has resulted in a distinctive religious tradition which is considerably different from that of other regions. While radicalism in Islam is a form of in-depth (radic) understanding in Islam. Instead of having the in-depth understanding of Islam, radical Islam is a form of Islamic understanding that tends to be "hard", scripturalistic, anti tradition and easily blame the interpretation of others. This has led to a movement that justifies any means to impose their views on others. They have even used violent acts, suicide bombings and other forms of violence. The rigid and scripturalistic understanding of Islam is such an antithesis of peaceful Islam Nusantara. The urgency of teaching Islam Nusantara in universities is such a must following the fact that some of the perpetrators of violence in the name of religion are educated groups from several leading universities. This indicates that the radical Islamic movement has begun to spread to higher education. Radicalism has widely been propagated especially to the students studying in non-Islamic studies vocational programs.Keywords: Islam Nusantara, radicalism, universities